Influence of demographics and motivational factors on US consumer clothing and shoes disposal behavior. (9th September 2019) - Rezaei Arangdad, Shaghayegh; Thoney-Barletta, Kristin; Joines, Jeff; Rothenberg, Lori
Abstract : Purpose: The purpose of this paper is to study clothing and shoes disposal behavior of US consumers in an attempt to understand how to divert more clothing and shoes from the landfill. Design/methodology/approach: A survey was administered to 209 consumers from the general US population. The survey includes questions on demographics, methods of disposal and factors that motivate or prevent consumers from choosing methods other than throwing unwanted clothing in the trash. Findings: Analysis of demographic data from the survey indicates that gender, income, marital status, living arrangement and type of dwelling have an effect on whether consumers recycle textiles. Other survey results indicate that helping factors are more influential in motivating consumers to recycle clothing and shoes than economic factors. The condition of clothes and shoes and lack of awareness are the most prominent reasons preventing consumers from recycling more textiles. The results also show that there are statistically significant differences between households with and without children when it comes to disposing adults' clothing and shoes. Originality/value: These results may help policymakers who want to motivate consumers to recycle or develop recycling programs.